Promoting rural energy technology: The case of gasifiers in the Philippines - Bernardo, Francisco P.; Kilayko, Gregorio U. (World development, 1990)
This paper provides an evaluation of the experience of diffusing gasifier technology in the Philippines. A field survey was carried out of 53 farmers’ groups involved with gasifiers in Panay Island in 1985. This was supplemented by information on the whole country which became available in 1987. Just over 1% (three out of 248 plants) were being used by 1987; over 80% were in need of repair and 16% were operational but unused. The research concludes that the problems were largely institutional, rather than inherent weaknesses in the technology. Success required a “fit” between technology, users and implementing agency: wood chip gasifiers appear preferable to those fueled by charcoal; many farmers saw little value in irrigation, let alone gasifier-powered pumps to lift irrigation water; charcoal was on occasion more scarce and more expensive than diesel; the implementing agency was inadequately funded and was subject to unrealistic installation targets imposed by the political system.